Overall risk index for patient transfers in total assistance mode executed by emergency medical technician-paramedics in real work situations. (January 2019) - Larouche, Dominique; Bellemare, Marie; Prairie, Jérôme; Hegg-Deloye, Sandrine; Corbeil, Philippe
Abstract: Few studies have quantified the risk of musculoskeletal disorders during patient transfers in total assistance mode in real-life prehospital emergency care situations. An index to assess the overall risk of patient transfers was created; it makes it possible to quantify risk based on the patient's position and the height of the patient's location. An analysis of 71 transfers executed by paramedics in actual work situations showed that moving a patient from the ground was characterized by acute sagittal flexions and axial rotations, respectively, 42% and 12% of the time. When the patient was lying on a raised surface, the lifting index and perceived exertion were the lowest (2.55; easy). According to the overall risk index, patient transfers from the ground are the riskiest. Paramedics execute many risky lifts even in favorable patient handling contexts. Highlights: Patient transferring is an activity at risk for MSDs. Six variables were combined to rate the overall risk of transfers. Overall risk is higher when the patient is moved from the ground. EMT-Ps execute many lifts even in favorable contexts. Possible solutions: technological development and training (know-how).